2022
DOI: 10.3390/cancers14184493
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Rapid On-Site Evaluation of Touch Imprint Cytology during Cryobiopsy for Peripheral Pulmonary Lesions

Abstract: Cryobiopsy enables us to obtain larger specimens than conventional forceps biopsy despite the caution regarding complications. This study aimed to evaluate the clinical utility of rapid on-site evaluation of touch imprint cytology (ROSE-TIC) during cryobiopsy of peripheral pulmonary lesions (PPLs). We retrospectively reviewed the data of consecutive patients who underwent cryobiopsy for solid PPLs between June 2020 and December 2021. ROSE-TIC was performed on the first specimen obtained via cryobiopsy and asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Furthermore, the clinical factor that affected the diagnostic yield of cryobiopsy using the ultrathin cryoprobes was the bronchus sign on TSCT, which is consistent with those previously reported for conventional biopsy devices [22,23]. As in previous reports of cryobiopsy, ROSE slide preparation was also possible using specimens obtained by non-intubated cryobiopsy [24,25]. In diagnosing PPLs with bronchoscopy, the primary purpose is often the collection of tumor cells, which have distinctive histopathological features that can be recognized even in small samples, from the precise location of the target lesion through the related bronchus [21,26,27].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the clinical factor that affected the diagnostic yield of cryobiopsy using the ultrathin cryoprobes was the bronchus sign on TSCT, which is consistent with those previously reported for conventional biopsy devices [22,23]. As in previous reports of cryobiopsy, ROSE slide preparation was also possible using specimens obtained by non-intubated cryobiopsy [24,25]. In diagnosing PPLs with bronchoscopy, the primary purpose is often the collection of tumor cells, which have distinctive histopathological features that can be recognized even in small samples, from the precise location of the target lesion through the related bronchus [21,26,27].…”
Section: Discussionsupporting
confidence: 86%
“…Muto et al 8 recently demonstrated that TIC-ROSE can be a suitable intraprocedural assessment tool for cryobiopsy, with a concordance rate of 76.2%. Their study was performed in a monomodality sampling setup using only cryobiopsy as the sampling T A B L E 2 Rapid on-site evaluation outcomes compared with procedural outcomes, N = 66.…”
Section: Discussionmentioning
confidence: 99%
“…Although, in endobronchial ultrasound (EBUS)-guided mediastinal lymph node staging, ROSE has had high concordance rates of 89%-96% and has been shown to reduce the amount of samples needed, 5,6 concordance rates of ROSE during navigation bronchoscopy have rarely been reported and vary widely, between 47.5% and 89.9%. 3,7,8 In the pulmonary care setting, ROSE is commonly used to examine cytology specimens obtained with transbronchial needle aspiration (TBNA) or a brush, and the use of ROSE for histologic samples is a valuable alternative and has been reported incidentally in studies. 9,10 The recently published joint guideline by Roy-Chowdhuri and colleagues 11 issued strong advice to include the use of touch imprint cytology (TIC) preparations of histologic samples for on-site evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations